Africa Agriculture Transformation Scorecard: performance and lessons. Mauritius - Greffiths, Ikhothatseng Jacob; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Fakudze, Bhekiwe (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2021)
This brief highlights Mauritius’ performance in the second BR and assesses challenges faced and lessons learned by the Mauritius during the review. The brief also reviews policy and programmatic changes in Mauritius which can be attributed to the first (2017) and second BRs and concludes by highlighting required policy actions for Mauritius to meet the Malabo commitments by 2025.